Analisis Kesulitan Siswa Dalam Menyelesaikan Bentuk Soal Cerita Satuan Panjang Kelas III SD - Zahra Saleha; Ani Nur Aeni; Nurdinah Nurhanifah; Ali Ismail; Atep Sujana; Maulana Maulana (Departement of Mathematics Education, 2024)
The aim of this research is to describe the analysis of student difficulties and the factors causing the difficulties experienced by students in solving long unit mathematics story problems for class III elementary school. This research uses qualitative descriptive research. The research subjects were three third grade elementary school students who were identified as having difficulty in solving story problems. Data collection techniques use observation, interviews, documentation and tests. The results of this research are that. Students experience difficulties, especially in reading comprehension, process skills, and encoding errors. The causal factors come from internal and external factors of students. For internal factors, such as students not understanding the questions, students not being careful enough, students not being used to story problems, and students not having enough practice in working on story problems. External factors, such as inappropriate methods, models, teaching aids and learning media used in learning, lack of motivation from the environment around students, and too much influence from gadgets.